Slab‐Plume Interactions Beneath Australia and New Zealand: New Insight From Whole‐Mantle Tomography - Toyokuni, Genti; Zhao, Dapeng (Geochemistry, geophysics, geosystems : G3, 2024)
Australia, New Zealand, and the surrounding regions have experienced complex plate interactions with significant seismic and volcanic activities. The Taupo volcano on the North Island of New Zealand has experienced multiple catastrophic eruptions. Although Australia is known as a stable landmass with low seismic and volcanic activity, intraplate volcanoes along its eastern coast are considered to be caused by hot mantle plumes. To better understand the seismic and volcanic activities in the region, it is necessary to study the detailed 3‐D structure of the crust and mantle. Here we apply a well‐established global tomography method to reveal the 3‐D P‐wave velocity (VP ${V}_{P}$) structure of the whole mantle beneath this region. We used ∼7 million P, pP, PP, PcP, and Pdiff wave arrival times of 23,666 earthquakes recorded at 14,181 seismograph stations worldwide. The resulting VP ${V}_{P}$ tomography clearly shows high‐VP ${V}_{P}$ subducted slabs, and low‐VP ${V}_{P}$ anomalies above and below the slabs, which may reflect corner flow in the mantle wedge and subslab hot mantle upwelling (SHMU), respectively. A slab window is revealed beneath the North Island of New Zealand. Given the development of SHMU beneath this region, the catastrophic eruptions of the Taupo volcano might be powered by a mixture of island arc magma and SHMU through the slab window. Beneath the intraplate volcanoes along the eastern coast of Australia and the Tasman Sea, a thin low‐VP ${V}_{P}$ zone exists and extends down to the core‐mantle boundary, suggesting that the intraplate volcanoes might be, at least partially, fed by a plume rising from the lower mantle. Plain Language Summary Australia, New Zealand, and their surrounding regions consist of the Australian Plate, the Pacific Plate, and many microplates located along their boundaries. Complex interactions among these plates result in significant seismic and volcanic activities. Especially, the Taupo volcano on the North Island of New Zealand has experienced multiple catastrophic eruptions. Furthermore, although Australia is known as a stable landmass with low seismic and volcanic activity, intraplate volcanoes along its eastern coast are considered to be associated with hot mantle plumes. To better understand the seismic and volcanic activities in the region, we investigated the 3‐D P‐wave velocity structure of the entire mantle beneath this region. The resulting tomography clearly shows subducted slabs, corner flow in the mantle wedge, and hot mantle upwelling below the slabs. An interesting feature is a possible slab window revealed beneath the Taupo volcano. The catastrophic eruptions of the Taupo volcano might be powered by a mixture of island arc magma and the subslab hot mantle upwelling through the slab window. Our tomography also suggests that the intraplate volcanoes along the eastern coast of Australia are, at least partially, fed by a plume rising from the lower mantle. Key Points Fine whole‐mantle tomography is determined beneath Australia and New Zealand Super‐eruptions of the Taupo volcano on the North Island of New Zealand might be related to a slab window Intraplate volcanoes in eastern Australia and the Tasman Sea are fed by a hot plume rising from the lower mantle